Faktor-Faktor Tekanan Kerja dan Hubungannya dengan Disiplin Rejimen Infantri, Tentera Darat Malaysia - Sukiman, Mohamed Ghani (2011)
The aim of this research to investigate the relationship and the influence of the job stress factors which include organisational factor (over loaded work), individual factor (communication barrier and discrimination) and environmental factor (environment work place) with the discipline of the regiment infantry. This research was conducted using cross sectional method which involved 388 respondents from four infantry battalions under command of 2nd Division Headquarters and 4th Division Headquarters. The data was analysed using Statistical Package for Social Science (SPSS) Version 17.0. Correlation analysis had shown a significant correlation between job stress factors with discipline in infantry regiment. Regression analysis shown that only two factors which is organisational factor and individual factor have an influence on discipline in regiment infantry.